CARYOPATHIC EFFECT OF BIO-PREPARATION BACILLUS SUBTILIS 12В ON THE STATUS OF SPERMATOGENIC EPITHELIUM OF ANIMALS INFECTED WITH HELMINTHS - E. V. Krasnikova; T. N. Sivkova; S. A. Shurakov (Российский паразитологический журнал, 2016)
Objective of research: to study the caryopathic effect of bio-preparation Bacillus subtilis 12В on the status of spermatogenic epithelium of white mice after a single intra-abdominal administration of the Fasciola hepatica extract. Materials and methods: The investigations were conducted on white male mice after oral use of preparation Sporovite based on B. subtilis 12B; then the intra-abdominal injection of F. hepatica extracts at a dose of 100 mkg/head was applied. The protein extract from F. hepatica was administered to mice of the second group, and animals of the third group received only the probiotic Sporovite. Animals of the fourth group did not get the preparation and served as controls. 48 hours later the animals were killed; touch smears obtained from testis were stained by the Romanovsky method and examined under a microscope what enables to determine the mitotic index and the number of pathological meiosis forms. The experiments were conducted on lambs whose seminal vesicles were placed into a solution of 10% Formalin and examined histologically. 2-3µ-thick slices were stained with Haematoxylin and Eosin by Van Gieson method and examined under a microscope at 50, 400 and 1000 x magnifications. Results and discussion: During the pathomorphological and caryomitotic studies of testis of white mice and lambs after administration of Sporovite on the background of intra-abdominal injection of F. hepatica extract the reduction of negative effects on the status of spermatogenic epithelium of testis in animals wasn’t observed. A decrease in mitotic index by 2-3 times and a high amount of pathological forms were registered. The number of metaphases with preterm chromosome disjunction under the joint effect of F. hepatica and B. subtilis extracts has decreased by half.